Przemoc językowa jako zachowanie towarzyszące grającym w gry cyfrowe - Granat, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The fact that linguistic violence is a phenomenon characteristic of computer game users has been observed by many researchers, mostly psychologists. They usually express their views on this subject on presumptive grounds. In this article, the author approaches the problem from the linguistic perspective. Analysis and interpretation of the statements of interlocutors is undertaken in order to extract linguistic exponents of violence from the verbal behavior during the game. The conclusions also include claims concerning the rationale behind the high popularity of digital games.